Iceland : 2010 Article IV Consultation and Third Review under Stand-By Arrangement and Request for Modification of Performance Criteria-Staff Report; Staff Supplement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Iceland. (IMF Staff Country Reports; Country Report ;, 2010)
Iceland's gross external debt rose above 600 percent of GDP, while households and corporations accumulated heavy debt burdens with large exposures to foreign exchange and inflation risk. The global banking crisis exposed Iceland's vulnerabilities, triggering a balance-of-payments crisis, a collapse of the exchange rate and output, and the failure of financial and many nonfinancial firms. The importance of accelerating the restructuring of banks' operations and balance sheets and also policy frameworks has been stressed. The downward trend in inflation is welcomed.